2021
DOI: 10.1177/14777606211062912
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basalt and polypropylene fibers on crumb rubber mortar with Portland cement and calcium aluminate cement binders: Strength and artificial neural network prediction model

Abstract: This paper aims to study the influence of basalt fiber (BF) and polypropylene fiber (PPF) in crumb rubber (CR) mortar made of two different types of cement, including ordinary Portland cement (OPC) and calcium aluminate cement (CAC). CR was used to partially (5%, 10%, 15%, and 20% by volume) replace the fine aggregate in OPC and CAC mortars. BF and PPF were added (0.1%, 0.3%, and 0.5% by total volume) in the CR mortars. The consistency, density, compressive, and flexural strength of cement mortars were investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Their findings indicate that a suitable substitution level of up to 30% using crumb rubber is deemed acceptable for aggregate replacement. These findings have verified the conclusions of numerous other recent investigations [23,24], which demonstrated that the transition zone between the cementitious matrix and the rubber aggregate is not very compact and has significant porosity. Consequently, these adhesion defects constitute weak points from which cracks can initiate under mechanical stress.…”
Section: Introductionsupporting
confidence: 90%
“…Their findings indicate that a suitable substitution level of up to 30% using crumb rubber is deemed acceptable for aggregate replacement. These findings have verified the conclusions of numerous other recent investigations [23,24], which demonstrated that the transition zone between the cementitious matrix and the rubber aggregate is not very compact and has significant porosity. Consequently, these adhesion defects constitute weak points from which cracks can initiate under mechanical stress.…”
Section: Introductionsupporting
confidence: 90%
“…The versatile quality of natural fibers are better compatibility, good thermosetting, and binding material due to its low density, good thermal insulation properties, improved mechanical properties, low prices, unavailability, easy to approaches, and free disposals, among several features (Baghban et al, 2022;Feng et al, 2022;Latifi et al, 2022;Marcalikova et al, 2020;Ruslan et al, 2022;Su et al, 2022). Although, the fact is that natural fibers have been broadly investigated in terms of their mechanical, thermal and morphological characteristics, like compressive and tensile qualities.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Today, the aim is to evaluate recycled rubber particles in concrete, with many studies aimed at developing rubberized concrete. [9][10][11][12][13] These rubber particles are used in three classes: chips, crumbs, and powder rubber. 14 Waste rubbers can be commercialized and used in asphalt, plaster, mortar, and concrete.…”
Section: Introductionmentioning
confidence: 99%